2020
DOI: 10.1111/jre.12726
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profile of genes related to immune response in generalized periodontitis

Abstract: Background and objective: Epigenetic events, as the DNA methylation, may be related to development of inflammatory diseases. Due to the important role of host's response in the pathogenesis of periodontitis, the purpose of the present study was to investigate the methylation profile of genes related to immune response in gingival tissues from patients with generalized periodontitis (GP) compared to healthy individuals.Methods: Gingival tissues were collected from 20 individuals with GP and 20 healthy individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…A prominent role in this context is attributed to epigenetic events, which induce changes in gene expression patterns without altering the DNA sequence [ 3 ]. These include DNA methylation, histone modification, chromatin remodelling and microRNA (miRNA) interference [ 4 , 5 ]. Epigenetic mechanisms play an important role in chronic inflammatory conditions, as observed in several diseases including cardiovascular disease, Alzheimer’s disease, rheumatoid arthritis and periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…A prominent role in this context is attributed to epigenetic events, which induce changes in gene expression patterns without altering the DNA sequence [ 3 ]. These include DNA methylation, histone modification, chromatin remodelling and microRNA (miRNA) interference [ 4 , 5 ]. Epigenetic mechanisms play an important role in chronic inflammatory conditions, as observed in several diseases including cardiovascular disease, Alzheimer’s disease, rheumatoid arthritis and periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In humans, research into epigenomic differences between patients with periodontal disease and periodontally healthy participants is limited and has focused mainly on candidate genes and epigenetic comparisons in gingival tissue. 17,18 Although the study of the epigenomic changes related to inflammatory process located at the periodontal tissue is very important to understand local inflammation in periodontitis, the tissue from a gingival biopsy with severe clinical inflammation and leukocyte infiltration would not be directly comparable with non-inflamed tissues in a periodontally healthy control subject, considering that the need of accounting for cellular heterogeneity in epigenetic studies has been largely demonstrated. 19,20 This problem can be approached via cell separation techniques; for example, Andia et al, using laser microdissection, separated epithelial and connective cell types in periodontal tissue making it possible to study DNA methylation differences in LINE1, SOCS1, and SOCS3.…”
Section: Introductionmentioning
confidence: 99%
“…There is now convincing evidence that epigenetic mechanisms such as DNA methylation are involved in the pathogenesis of periodontitis [9]. For example, it has been reported that tissue affected by periodontitis and normal periodontal tissue show differences in the methylation status of promoters for inflammation-related genes such as those encoding interleukin (IL)-8, tumor necrosis factor-alpha (TNFα) and toll-like receptor-2 (TLR2) [10][11][12][13]. Furthermore, increased methylation of the TLR2 promoter has been reported in a mouse model of periodontitis caused by infection with Porphyromonas gingivalis [7].…”
Section: Introductionmentioning
confidence: 99%